2011
DOI: 10.1021/am201087r
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Gold–Silica Nanostructures for Ultrasensitive Electrochemical Immunoassay of Streptomycin Residues

Abstract: A facile and simple electrochemical immunoassay for ultrasensitive determination of streptomycin residues (STR) in food was designed by using nanogold-assembled mesoporous silica (GMSNs) as bionanolabels on a three-dimensional redox-active organosilica-functionalized sensing interface. To construct such a sensing interface, we initially synthesized organosilica colloids by using wet chemical method, and then utilized the prepared colloidal organosilica nanocomposites for the immobilization of monoclonal anti-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…In another study, Liu et al [ 87 ] reported a simple electrochemical immunoassay for the sensitive detection of streptomycin. For the fabrication of the biosensor, monoclonal anti-STR antibodies were immobilized onto an organosilica colloid nanocomposite.…”
Section: Electrochemical Biosensors For Antimicrobial Drug Residuementioning
confidence: 99%
“…In another study, Liu et al [ 87 ] reported a simple electrochemical immunoassay for the sensitive detection of streptomycin. For the fabrication of the biosensor, monoclonal anti-STR antibodies were immobilized onto an organosilica colloid nanocomposite.…”
Section: Electrochemical Biosensors For Antimicrobial Drug Residuementioning
confidence: 99%
“…As they also exhibit good biocompatibility toward biologically active molecules, nano-SiO 2 particles represent excellent carriers for the immobilization of proteins and enzymes in electrochemical biosensors [131]. For example, Hong et al [132] prepared ferrocene-coated SiO 2 nanoparticles using oil-in-water technology to form stable, homogeneous, biocompatible, and highly surface active interfaces to effectively immobilize the antibodies in a no-reagent electrochemical immunosensor.…”
Section: Electrochemical Immunosensors Based On Various Nanomaterialsmentioning
confidence: 99%
“…This new type of label for immunosensors may provide many potential applications for the detection of the growth hormone in animal derived food. Another immunosensor application in food technology was carried out by Liu et al (2011). A facile and simple electrochemical immunoassay for ultrasensitive determination of streptomycin residues (STR) in food was designed.…”
Section: Mesoporous Materials As Sensors In Foodmentioning
confidence: 99%